2020
DOI: 10.1155/2020/4956179
|View full text |Cite
|
Sign up to set email alerts
|

Electroacupuncture Inhibits the Activity of Astrocytes in Spinal Cord in Rats with Visceral Hypersensitivity by Inhibiting P2Y1 Receptor‐Mediated MAPK/ERK Signaling Pathway

Abstract: Background. Irritable bowel syndrome (IBS) is a chronic functional bowel disease characterized by abdominal pain and changes in bowel habits in the absence of organic disease. Electroacupuncture (EA) has been shown to alleviate visceral hypersensitivity (VH) in IBS rat models by inhibiting the activation of astrocytes in the spinal cord. However, the underlying molecular mechanisms mediated by P2Y1 receptor of this effect of electroacupuncture remain unclear. Aim. To explore whether EA inhibits the activity of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 54 publications
2
12
0
Order By: Relevance
“…The analgesic effect of EA on visceral hypersensitivity has been extensively demonstrated (40)(41)(42)(43)(44), and the results of our study are consistent with this. EA reduced AWR scores and increased PWT, indicating that EA attenuated the visceral sensitization and peripheral mechanical hyperalgesia of PI-IBS.…”
Section: Discussionsupporting
confidence: 91%
“…The analgesic effect of EA on visceral hypersensitivity has been extensively demonstrated (40)(41)(42)(43)(44), and the results of our study are consistent with this. EA reduced AWR scores and increased PWT, indicating that EA attenuated the visceral sensitization and peripheral mechanical hyperalgesia of PI-IBS.…”
Section: Discussionsupporting
confidence: 91%
“…that regard, studies have shown the ability of EA to regulate inflammatory substance release and glial cell activation in the spinal cord. [37][38][39] In the present study, immunohistochemistry showed that GFAP and Iba1 expressions in the L5-S2 segments were enhanced in the dorsal horn of the spinal cord among the model group rats. In contrast, EA treatment showed an inhibitory effect on the activation of two immune related cells in the spinal cord among the EA group rats.…”
supporting
confidence: 56%
“…59 In addition to the local inflammation evoked by acetic acid, the role of spinal inflammatory reaction, including glial activation and pro-inflammatory cytokines release, in acetic acidinduced writhing response has also been reported. [60][61][62] Previous studies verified that both minocycline and fluorocitrate were able to markedly reduce acetic acid-induced acute visceral nociception. 62,63 In this point, we for the first time provided evidence that ulinastatin inhibited the activity of microglia and astrocytes in the spinal cord with visceral pain.…”
Section: Discussionmentioning
confidence: 96%
“…[60][61][62] Previous studies verified that both minocycline and fluorocitrate were able to markedly reduce acetic acid-induced acute visceral nociception. 62,63 In this point, we for the first time provided evidence that ulinastatin inhibited the activity of microglia and astrocytes in the spinal cord with visceral pain.…”
Section: Discussionmentioning
confidence: 96%